Transformation of Health Service Employee Performance: Case Study of Gribig Health Center, Malang City - Ramadhani, Dyon Seno; Renanda, Feby Farisya (PANGRIPTA, 2024)
This study aims to analyze the transformation of employee performance in the health service sector through individual characteristics and work ethic, with a case study at the Gribig Health Center, Malang City. The study used a quantitative method with Covariance-Based Structural Equation Modeling (CB-SEM) analysis to test the direct and indirect effects of these variables on employee performance. Data were collected through questionnaires distributed to 35 employees of the Gribig Health Center, Malang City, Malang Regency. The results showed that work ethic had a significant effect on employee performance, while individual characteristics had a significant effect through the mediating role of organizational commitment. This study provides insight that improving employee performance in the health sector can be achieved through strengthening work ethic and managing individual characteristics effectively, with organizational commitment as an important link.